Management of a Case of Dengue Shock Syndrome with Liver Failure: A Case Report - Nafi, Ahmad; Begum, Momtaz; Dristy, Nazrana Ahmed; Nihal, Tanjim Abid; Islam, Md Saiful; Hussain, Tasnim (Journal of Bangladesh College of Physicians and Surgeons, 2023)
This case report details the management and treatment of a 38-year-old male cook from Dhaka, diagnosed with dengue fever, which progressed to Dengue Shock Syndrome (DSS) accompanied by acute liver failure. Despite initial stabilization with fluid resuscitation, patient’s condition worsened, prompting a fresh whole blood transfusion and comprehensive care. This report underscores the necessity of prompt recognition and effective management of severe dengue cases to improve patient outcomes J Bangladesh Coll Phys Surg 2023; 41: 114-117